Parathyroid hormone-related protein in rat penis: expression, localization, and effect on cavernosal pressure - Lang, Hervé; Endlich, Nicole; Endlich, Karlhans (Endocrinology, 1999)
Although PTH-related protein-(1-36) [PTHrP-(1-36)] is known to be expressed in smooth muscle and to exert potent myorelaxant effects, its tonic effects on cavernosal smooth muscle has not yet been explored. Using the RT-PCR technique, the present study establishes that PTHrP messenger RNA is present in microdissected corpus cavernosa in the rat. In immunohistochemical studies using affinity-purified antibodies to middle regions of PTHrP, immunostaining was localized throughout the penile structures, including vessels, cavernosal smooth muscle, and trabecular fibroblasts. Strong immunostaining for PTHrP was also detected in the dorsal nerve bundles. In anesthetized rats, intracavernosally injected boluses of increasing doses of PTHrP-(1-36) (0.3-30 pmol in 100 μl saline) had little effect on intracavernosal pressure. However, they markedly potentiated the dilatory response to papaverine (8-800 nmol), increasing the papaverine-induced intracavernous pressure by 2.5-fold, close to the mean arterial pressure. In conclusion, the cavernosal expression of PTHrP messenger RNA, the distribution of immunoreactive PTHrP throughout the structuro-functional components of the erectile apparatus and its strong potentiating action on papaverine-induced cavernosal relaxation, collectively suggest that PTHrP participates in the control of cavernosal tone.
Gesehen am 23.10.2017